JEP 2020
DOI: 10.7176/jep/11-15-12
|View full text |Cite
|
Sign up to set email alerts
|

School Performance and Leadership Styles Nexus: Exploring the Mediation Effect of Teacher Job Satisfaction in the Public Senior High Schools in Ghana

Abstract: The increasing complexities of school settings and global educational reforms, school leadership has been recognized to play a key role in school performance worldwide. Nonetheless, the mechanisms through school leaders contribute to school performance has not been fully established till date especially due to difference in context of study, regional and cultural convolutions. To address this research lacuna, the study investigated the extent to which leadership styles directly and indirectly contribute teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Males and females are equal in their approach to science, and inequality in science education and science is caused by educational, political, and social factors external to science. This study underscores the necessity of providing males and females with equitable opportunities and challenges, along with access to high-quality education (Gyimah, 2020). It also reveals that females who lack confidence exhibit impaired causal attribution patterns, view mathematics as a predominantly male domain, and experience heightened levels of anxiety when engaging with the subject (Abrehet al, 2018;Breda & Napp, 2019).…”
Section: The Participantsmentioning
confidence: 69%
See 1 more Smart Citation
“…Males and females are equal in their approach to science, and inequality in science education and science is caused by educational, political, and social factors external to science. This study underscores the necessity of providing males and females with equitable opportunities and challenges, along with access to high-quality education (Gyimah, 2020). It also reveals that females who lack confidence exhibit impaired causal attribution patterns, view mathematics as a predominantly male domain, and experience heightened levels of anxiety when engaging with the subject (Abrehet al, 2018;Breda & Napp, 2019).…”
Section: The Participantsmentioning
confidence: 69%
“…Numerous factors contribute to the gender inequalities in mathematics and attitude (Armah et al, 2021). In this study, we perceive six primary characteristics that have been shown to influence students' attitudes toward mathematics these include teacher attitudes and beliefs (Owan et al, 2019;Poku, 2021), teaching style and behaviour, teaching techniques (Azila-Gbettor & Abiemo, 2021;Gyimah, 2020) achievement (Abreh et al, 2018;Nsalamba & Alex, 2019), parent attitudes and beliefs (Nsalamba & Alex, 2019;Owan et al, 2019), and students classroom experiences (Breda & Napp, 2019;Nsalamba & Alex, 2019;Spaull & Makaluza, 2019), as having a significant impact, influencing the extent to which females believe they are not as capable in math as males. Findings from studies exploring classroom environments have shown that teachers' behaviours play a crucial role in shaping students' attitudes towards mathematics (Ghasemi & Burley, 2019).…”
Section: Research Problemmentioning
confidence: 99%